Creative imagination and creativity - Di Gregori, María Cristina (2018)
In the last decades the idea of creativity has gained increasing interesting in the field of philosophy, cognitive sciences, sociology, etc. and there have been renewed contribution regarding the classic idea of creativity. We consider the contribution of classic pragmatism deserve special mention – particularly in the works of Charles. S. Peirce and John Dewey. In this article, we are going to refer exclusively to the Deweyan treatment of this idea. We will sustain that Dewey’s theory provides interpretative elements which are innovative and disruptive regarding the philosophical tradition including a novelty conception of creative imagination. We will expose some consequences of his position – as we interpret it. In effect, we are going to sustain that Dewey moves away from classic demands to which a creative product involves, necessarily a radical transformation of human life, according with the idea of degrees of creativity; that Deweyan’s theory constitute an interesting insight for promoting the creative attitude; that the creative process retains the same structure in all cases - science and art, for example - and that creativity is now an intrinsic potentiality of human beings - which may be realized or not. Finally, we consider the relevance of some Deweyan thesis for nowadays positions, as in the case of the cognitive psychologist Robert Weisberg, emphasizing their coincidences and disagree.